Detection of two different tumor types in dog oral cavity: Case report (Research, Society and Development, 2021)
The oral cavity represents the fourth most frequent site of neoplasms, being responsible for approximately 5% of tumors in dogs. Its occurrence is higher in animals with medium to advanced age, being also observed in young animals. The purpose of this report was to describe two distinct tumor types identified in a dog's oral cavity, with emphasis on individual histopathological examination, for different masses in the same anatomical region. A Golden Retriever dog was evaluated and a specific examination of the oral cavity showed halitosis, periodontal disease grade III and the presence of new formation in the maxillary cheek mucosa and mandibular mucosa, both on the left side. The animal was sent for mass excision, using the classic surgical technique and the fragments were sent for histopathological analysis, which showed melanocytic melanoma in the mandibular mucosa and mastocytoma in the maxillary mucosa of the maxilla, both on the left side. The postoperative period consisted of cleaning the oral cavity twice daily with periogard®, for ten days, stomorgyl 20®, 3 tablets, SID, for 7 days, maxicam® 2 mg, 2 tablets, SID, for 3 days and tramadol 50 mg, 2 tablets, BID, for 5 days, all orally. On the 10th postoperative day, the animal returned for evaluation, where good healing was observed at the lesion excision site, on that occasion an electrochemotherapy session with bleomycin sulfate was performed, in the region of the surgical scar. At 30 days after the operation, the animal was well, with good food and no recurrence of lesions in the oral cavity. This study reinforces the need for rapid diagnosis and therapeutic adoption, in order to maintain quality and increase the life expectancy of patients who present with neoplasia in the oral cavity. The performance of an individual histopathological examination, in different masses in the same anatomical region, is essential in order to correctly identify the tumor type and establish the treatment, which may include classical surgical excision or use adjuvant therapies, such as electrochemotherapy.